Thinking Goes Back to School: Providing Better Vision Therapy to Patients with Autism Spectrum Disorder. - Coulter, Rachel Anastasia; Tea, Yin C.; Wieder, Serena (Optometry & Visual Performance, 2014)
Background: Autism Spectrum Disorder (ASD) is a developmental disability characterized by difficulties in social interaction and sensory processing. When vision therapy is indicated, the optometrist may be challenged to provide a vision therapy program that the patient can successfully complete or that produces results that generalize to more naturalistic settings due to challenges associated with ASD. Methods: From a series of case vignettes, challenges in providing vision therapy are identified. Drawing upon the DIR Model/Floortime and Visuo-Cognitive Therapy, clinical strategies are presented to address these challenges so that the patient can succeed in a vision therapy program. Results: Ten clinical pearls for providing vision therapy to patients with ASD are summarized. Conclusions: The DIR Model/Floortime and Visuo-Cognitive Therapy offer optometrists additional tools and strategies to enhance vision therapy provided to patients with ASD.